PERUVIAN POPULAR LANGUAGE IN RESPLANDOR DE NOVIEMBRE (“NOVEMBER GLOW”) OF ABELARDO SÁNCHEZ LEÓN - Martos Carrera, Marco (2013)
Abelardo Sánchez León is a noted author who writes poetry and novels. This paperdraws attention to the reliable use of popular language of the Spanish of Peru in his latest novel published in 2013. The text says that apart from the literaryenjoyment, the reader can find vivid examples of the speech of Peru in the lastthirty years.